Audit Pemasaran Dan Pengembangan Usaha Mikro, Kecil dan Menengah Di Dusun Koloh Berora Kabupaten Lombok Utara - Baiq Nurul Suryawati; Iwan Kusmayadi; Laila Wardani; Sulaeman Sarmo; I Nyoman Nugraha Ardana Putra (Jurnal Gema Ngabdi, 2020)
A marketing audit is needed to facilitate business owners who have difficulty developing business activities in the Koloh Berora hamlet. This effort was made to change the traditional marketing concept of business owners who are only oriented towards passive marketing. Passive marketing is characterized by the lack of business from the owners of various types of businesses in the village of Koloh Berora to recognize consumers. Most businesses actually run just because they join in. A simple marketing audit effort is carried out through various method for example: focus group discussion, best practice, and brainstorming to observe what products consumers like, the simple thing is to keep evidence of frequent order records. This inventory inventory effort is expected to help business owners to better identify their customers. Discipline in recording or archiving stock books is an important key to the success of the marketing audit. Further business development can be identified if the business owners have a high commitment to continue the marketing audit process itself.